2018
DOI: 10.3390/ijms19030730
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Th17 versus Treg Cells in Autoimmunity

Abstract: T helper type 17 (Th17) cells and pTreg cells, which share a common precursor cell (the naïve CD4 T cell), require a common tumor growth factor (TGF)-β signal for initial differentiation. However, terminally differentiated cells fulfill opposite functions: Th17 cells cause autoimmunity and inflammation, whereas Treg cells inhibit these phenomena and maintain immune homeostasis. Thus, unraveling the mechanisms that affect the Th17/Treg cell balance is critical if we are to better understand autoimmunity and tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
474
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 580 publications
(487 citation statements)
references
References 125 publications
6
474
3
4
Order By: Relevance
“…62 Other studies showed that Foxp3 + T cells could lose Antigen-4 and Foxp3. 30 A study of rejection after transplantation indicated that 1,25(OH) 2 D 3 30 A study of rejection after transplantation indicated that 1,25(OH) 2 D 3…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…62 Other studies showed that Foxp3 + T cells could lose Antigen-4 and Foxp3. 30 A study of rejection after transplantation indicated that 1,25(OH) 2 D 3 30 A study of rejection after transplantation indicated that 1,25(OH) 2 D 3…”
Section: Discussionmentioning
confidence: 99%
“…64 According to Fawaz et al, 63 vitamin D reduced the expression of Th17 markers and secretion of the pro-inflammatory cytokines IL-17A and Interferon-γ. 30 for Treg cells transform into Th17 cells in an inflammatory environment is a real concern because these phenotypes have the potential to exacerbate the condition. 30 for Treg cells transform into Th17 cells in an inflammatory environment is a real concern because these phenotypes have the potential to exacerbate the condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells produce the signature cytokines interleukin‐17 (IL‐17), and to a lesser extent tumor necrosis factor‐α (TNF‐α), IL‐23, and IL‐6. IL‐17 can also stimulate macrophages to produce inflammatory cytokines, such as IL‐6, TNF‐ a, and IL‐1b . Zhu et al demonstrated that IL‐17 not only promotes the production of large amounts of vWF by vascular endothelial cells, but also induces apoptosis of vascular endothelial cells through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…REFERENCES:[1] Miyakis S, et al J Thromb Haemost. 2006;4(2):295-306[2] Sciascia S, et al Thromb Haemost.…”
mentioning
confidence: 99%